2016
DOI: 10.18533/rss.v1i3.25
|View full text |Cite
|
Sign up to set email alerts
|

A Review on The Perpetrators of Child Abuse

Abstract: A review of the studies related to the perpetrators of child abuse revealed that each minimal unit of human being has the potential to perpetrate. Based on this, the present study aimed to comprehend the factors of vulnerability among the perpetrators of the child abuse. The study followed a method of investigating through the reviews of articles and research papers, on the issues of child abuse and perpetrations, published between 1994 and 2015, open source. The identified factors of vulnerability included ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
(37 reference statements)
3
10
0
Order By: Relevance
“…7 A review on the perpetrators of child abuse done by Santhosh in 2016 noted that any human being is capable of abuse, but risk factors include age: on the average at late 20s to early 30s, circumstances during abuse such as the victim being alone with the perpetrator, personality type including lack of self-confidence and reduced impulse control, and history of childhood abuse. 8 Studies on female perpetrators are very limited, since they are usually labeled as the victim. A study in Canada in 2017 on female assailants in child sexual abuse cases reported that majority of victims were of female gender with age approximately 10 years old and were mostly a member of the family.…”
Section: Discussionmentioning
confidence: 99%
“…7 A review on the perpetrators of child abuse done by Santhosh in 2016 noted that any human being is capable of abuse, but risk factors include age: on the average at late 20s to early 30s, circumstances during abuse such as the victim being alone with the perpetrator, personality type including lack of self-confidence and reduced impulse control, and history of childhood abuse. 8 Studies on female perpetrators are very limited, since they are usually labeled as the victim. A study in Canada in 2017 on female assailants in child sexual abuse cases reported that majority of victims were of female gender with age approximately 10 years old and were mostly a member of the family.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of a perpetrator were based on 3 levels: individual, relationship and community. Since decades ago, the characteristics of a child abuse perpetrator have been classified into different categories (30,31). Nevertheless, they still fall into similar context of classification across the diverse groups of characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Perpetrators Santhosh (2016) in his research that correlated to the perpetrators of child abuse exposed that every person could be vulnerable to these abuses. Besides, the annual statistic report Department of Social Welfare under the section of children in need of care and protection stated that the perpetrator could be parents, child's partner, caregivers, child's relatives, step-parent or foster parents, and others.…”
Section: Criteria That Contributes To Factors Of Child Abusementioning
confidence: 99%